Water quality evaluation in Tigre and Rincón rivers of península de Osa in two different periods of time - Calvo-Brenes, Guillermo (2015)
Península of Osa is a region characterized by a high biodiversity in plants and animals, as well. Hydric resources are not only an indicator of economic and social condition of a region but also related to protection of plants and animals. Costa Rica is privileged by the many rivers and ground waters it has; but the contamination levels are increasing alongside and península of Osa does not scape to that country reality. The objective of this research was to evaluate the quality of two important rivers of the peninsula: Tigre and Rincón rivers in two different periods of time in order to verify if rivers quality has changed during the time evaluated. Contamination levels were determined by the Dutch Index and Fecal Coliforms content in waters. On each river the evaluation was done in the upper side and the lower side since social and environmental conditions are different. The periods of time selected for evaluation were 2008-2009 and 2010-2011. Besides, data collected was separated in two seasons: summer and winter, so that statistical analysis can be performed using the statistical software SPSS. It was found that Fecal Coliforms content during summer time is such that recreational activity of first contact is allowed in those two periods of time. On the other hand, the Fecal Coliforms content during winter of 2009 exceeded the limits so recreational activity is not allowed. In general, the Fecal Coliforms content in 2011 were below the limits, except for the upper side area in July for Tigre river(Ti-1) and the lower side area in June for Tiger river (Ti-3). The contamination levels of each sampled zones ranges the No Contamination level and Little Contamination level when evaluated through the Dutch Index. Statistical analysis does not show any statistical difference between summer and winter or between time periods (2008-2009 and 2010-2011). The only exception is the lower side of Tigre river (Ti-3) that shows a statistical increase in the contamination level between the two time periods evaluated during winter.